2002
DOI: 10.1071/ar01191
|View full text |Cite
|
Sign up to set email alerts
|

Diets containing high-quality animal proteins increase growth of early-weaned pigs

Abstract: A production experiment was conducted with 96 fourteen-day-old weaned male piglets to compare diets containing preparations of freeze-dried porcine plasma (P) and freeze-dried bovine colostrum (C) for 35 days after weaning. These diets were compared with a diet consisting of soybean meal (SP) and a diet with animal protein sources (AP). All diets contained varying proportions of bloodmeal, fishmeal, meat and bone meal, and skim milk powder. The levels of colostrum and porcine plasma were reduced from 60 g/kg t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Our results on the capacity of bovine colostrum to limit weaninginduced growth check of piglets during the colostrum feeding period were partially in agreement with literature data. Studies with large-sized experimental groups reported moderate effects on growth performance, essentially an increased ADG (Pluske etal., 1999;Dunshea et al, 2002;Boudry et al, 2008). Other researchers reported no modification of these criteria; however, these studies seemed to be conducted with an animal number inadequate to evaluate effects on growth performance (Boudry et al, 2007a;King et al, 2007King et al, , 2008a.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our results on the capacity of bovine colostrum to limit weaninginduced growth check of piglets during the colostrum feeding period were partially in agreement with literature data. Studies with large-sized experimental groups reported moderate effects on growth performance, essentially an increased ADG (Pluske etal., 1999;Dunshea et al, 2002;Boudry et al, 2008). Other researchers reported no modification of these criteria; however, these studies seemed to be conducted with an animal number inadequate to evaluate effects on growth performance (Boudry et al, 2007a;King et al, 2007King et al, , 2008a.…”
Section: Discussionmentioning
confidence: 84%
“…Most of those studies examined effects of a decreasing amount of bovine colostrum. Indeed, Dunshea et al (2002) reported increased ADG and ADFI, but not G:F, in piglets fed a bovine colostrum-supplemented diet during the first 7 d but not later during the additional 14 d of colostrum supplementation. This difference corresponded to a transition ofthe bovine colostrum rate from 6 to 2.5%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is because bovine colostrum contains high levels of immunoglobulins and growth factors such as IGF-1, and may be viewed as a "safer" product to feed than animal plasma. Dunshea et al (2002) compared diets containing preparations of freeze-dried porcine plasma and freeze-dried bovine colostrum after weaning at 14 days of age. These diets were compared with a diet consisting of soybean meal and a diet with animal protein sources.…”
Section: Plasma Proteins and Its Alternativesmentioning
confidence: 99%
“…Similar to spray-dried plasma, dietary inclusion of spray-dried bovine colostrum has been shown to improve feed intake and growth rate during the post-weaning period (Pluske et al, 1999b;Dunshea et al, 2002). Given the similarity between these two products, the same immunological mechanism of action may underlie the effects of each.…”
Section: Introductionmentioning
confidence: 95%